The intensity of COVID-19 Non-Pharmaceutical Interventions and labor market outcomes in the public sector - Miriam Marcén; Marina Morales (Global Labor Organization (GLO), 2020)
This paper examines whether the intensity of Non-Pharmaceutical Interventions (NPIs) during the COVID-19 pandemic has differentially impacted the public sector labor market outcomes. This extends the analysis of the already documented negative economic consequences from COVID-19 and their dissimilarities with a typical economic crisis. To capture the intensity of the NPIs, we build a novel index (COVINDEX) using daily information on NPIs merged with state level data on out of home mobility (Google data) to show that among individuals living in a typical state, the NPIs enforcement during the COVID-19 reduces the likelihood of being employed (at work) by 5% with respect to the pre-COVID period and the hours worked by 1.3% using data on labor market outcomes from the monthly Current Population Survey and difference-in-difference models. This is a sizable amount representing the sector with the higher job security during the pandemic. Public sector workers in a typical state are 4 percentage points more likely to be at work than salaried workers in the private sector and 7 percentage points more likely than self-employed workers (the worst so far). Our results are robust to endogeneity of the NPIs measures and present empirical evidence of heterogeneity in the response to the NPIs with those in the local employment being the hardest hit.
Keywords: D1; J15; J16; J2; J23; J45; 330; COVID-19; coronavirus; public sector; remote work; essential worker; employment; hours worked